Prevalence of Primary and Secondary Resistant Mutations to Antiretroviral Drug in a Population of Puerto Rican Infected with HIV - Torres-Rivera, Betzy; Vallés, Victor; Ríos-Olivares, Eddy (Puerto Rico Health Sciences Journal, 2012)
see manuscript